Acetaminophen is both bronchodilatory and bronchoprotective in human precision cut lung slice airways. (2nd September 2019) - Kennedy, Joshua L.; Kurten, Richard C.; McCullough, Sandra; Panettieri, Reynold A.; Koziol-White, Cynthia; Jones, Stacie M.; Caid, Katherine; Gill, Pritmohinder S.; Roberts, Dean; Jaeschke, Hartmut; McGill, Mitchell R.; James, Laura
Abstract: Epidemiologic studies have demonstrated an association between acetaminophen (APAP) use and the development of asthma symptoms. However, few studies have examined relationships between APAP-induced signaling pathways associated with the development of asthma symptoms. We tested the hypothesis that acute APAP exposure causes airway hyper-responsiveness (AHR) in human airways. Precision cut lung slice (PCLS) airways from humans and mice were used to determine the effects of APAP on airway bronchoconstriction and bronchodilation and to assess APAP metabolism in lungs. APAP did not promote AHR in normal or asthmatic human airways ex vivo . Rather, high concentrations mildly bronchodilated airways pre-constricted with carbachol (CCh), histamine (His), or immunoglobulin E (IgE) cross-linking. Further, the addition of APAP prior to bronchoconstrictors protected the airways from constriction. Similarly, in vivo treatment of mice with APAP (200 mg/kg IP) resulted in reduced bronchoconstrictor responses in PCLS airways ex vivo . Finally, in both mouse and human PCLS airways, exposure to APAP generated only low amounts of APAP-protein adducts, indicating minimal drug metabolic activity in the tissues. These findings indicate that acute exposure to APAP does not initiate AHR, that high-dose APAP is protective against bronchoconstriction, and that APAP is a mild bronchodilator.